DIRECT EFFECT OF ELASTIC ADHESIVE WITH CORRECTION TECHNIQUE AND MUSCLE FACILITY ON DYNAMIC BALANCE IN CHRONIC ANKLE INSTABILITY INJURY AT PARAPAT HOSPITAL - I Ngurah Gede Verar Fujastawan; Isaharpika Br Ginting; Noni Herawati; Vicktor Henry Rony Apituley (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Objective: To seethedirecteffectofkinesiotape (KT) with correction and facilitation techniques after ten minutes of dynamic balance using the star excursion balance test (SEBT) on chronic ankle instability injury (CAI). Subjects: 111 subjects were divided into group 1 correction techniques (n = 21), group 2 facilitation techniques (n = 26), andgroup 3 controls normal (n = 64). Method: quasi experimental randomized controlled trial by testing the SEBT percentage pre-postgroup 1 andgroup 2, and testing the SEBT percentage after 10 minutes in groups 1 and 2 compared to the normal 3-ankle group. Result: paired sample t- testpre (87.62% ± 9,631) and post (98.14% ± 10,556) group 1 p = 0,000 (p <0.005) there is difference of dynamic balance, paired sample t-test pre (90, 12.5% ± 8,529) and post (96.5% ± 14.049) group 2 p = 0.015 (p < 0.05) there is difference of dynamic balance, independent sample t-test post group 1 and group 2 p = 0.659 (p> 0.05) and ANOVA group 1, group 2, & group 3 (95.13% ± 11.31) p = 0.585 (p> 0.05) there is no difference of dynamic balance. Conclusions: Both techniques of KT on ankle have a neuro-physiological effect on dynamic balance same US normal ankle.